Association of Weight Status and Energy & Macronutrient Intake with the Academic Performance of Female Student of RLAK Govt College of Home Economics Karachi - Asar, Farzana; Saeed, Perveen (Nurture, 2016)
Nutritional Nutritional depletion is a serious international problem that can lead to long-term deficits in growth, immune function, cognitive and motor development, behavior, and academic performance. The purpose of this study was to explore the association between weight status and Energy & Macronutrient Intake and academic performance of young female college students (18-24 years). A questionnaire consisting of items regarding subjects’ general information, food intake, and academic records was used as a data collection tool. Information about food intake was collected by quantitative food frequency questionnaire and was used to assess food and nutrient intake. Underweight students were more likely to have poor academic performance but the difference was not significant. There was a significant positive association between protein and energy intake and the academic performance of the students (p=.037 & 0.005 respectively). The proportion of students having below average performance was lower in the group that had adequate protein and energy intake.